Let us solve the differential equation "\\frac{dy}{dx}=\\frac{2x^2+y^2}{-2xy+3y^2}," which is equivalent to "\\frac{dy}{dx}=\\frac{2+(\\frac{y}{x})^2}{-2\\frac{y}{x}+3(\\frac{y}{x})^2}." Let us use the transformation "y=ux." Then "\\frac{dy}{dx}=\\frac{du}{dx}x+u." We get the equation "\\frac{du}{dx}x+u=\\frac{2+u^2}{-2u+3u^2}," which is equivalent to "\\frac{du}{dx}x=\\frac{2+u^2}{-2u+3u^2}-u," and hence to "\\frac{du}{dx}x=\\frac{2+u^2+2u^2-3u^3}{-2u+3u^2}." Then we have the equation "\\frac{-2u+3u^2}{2+3u^2-3u^3}du=\\frac{dx}{x}." It follows that
"\\int\\frac{-2u+3u^2}{2+3u^2-3u^3}du=\\int\\frac{dx}{x}"
"-\\frac{1}{3}\\int\\frac{6u-9u^2}{2+3u^2-3u^3}du=\\int\\frac{dx}{x}"
"-\\frac{1}{3}\\int\\frac{d(2+3u^2-3u^3)}{2+3u^2-3u^3}=\\int\\frac{dx}{x}"
"\\ln|x|=-\\frac{1}{3}\\ln|2+3u^2-3u^3|+\\ln|C|"
"\\ln|x|+\\frac{1}{3}\\ln|2+3u^2-3u^3|=\\ln|C|"
"\\ln|x(2+3u^2-3u^3)^{\\frac{1}{3}}|=\\ln|C|"
"x\\sqrt[3]{2+3u^2-3u^3}=C"
"x\\sqrt[3]{2+3(\\frac{y}{x})^2-3(\\frac{y}{x})^3}=C"
"\\sqrt[3]{2x^3+3y^2x-3y^3}=C"
It follows that the general solution of the differential equation "\\frac{dy}{dx}=\\frac{2x^2+y^2}{-2xy+3y^2}" is
"2x^3+3y^2x-3y^3=C."
Comments
Leave a comment